CLASSIFICATION OF EMOTIONS OF THE CHARACTERS DADANG AND DUDUNG IN THE PLAY LAA TAGDHOB BY AZIS MOA (LITERARY PSYCHOLOGY STUDY) - Pradita, Putri Trian; Silviani; Putra, Adita Widara (Media Inovasi Pendidikan dan Publikasi, 2024)
The play Laa tagdhob by Azis Moa contains various types of emotions from each character, however, Dadang and Dudung are more dominant characters where they are the main characters of the story. This research uses a qualitative descriptive method. The qualitative descriptive method is a research method that is decomposed in the form of words not numbers and also develops an inductive mindset so that in the process of answering a problem it does not necessarily rest on theories, axioms, and principles as existing truths, but on facts that arise naturally in the field. The purpose of this research is to find out the emotions in the text and then classify them using Boeree's emotion theory. The data collection technique is content analysis whose data source is from the play Laa Tagdhob by Azis Moa. The data that has been collected is then analyzed using a literary psychology approach which focuses on classifying the emotions of the two main characters in the play Laa Tagdhob. This literary psychology theory is used to analyze the formulation of research problems. The results of the research that have been carried out based on the data in the Laa Tagdhob drama script found 7 classifications of emotions from the two characters Dadang and Dudung, namely the family of surprise, fear, anger, sadness, desire, happiness, and boredom.